INVESTIGATION OF THE EFFECT OF Mn IMPURTTY ON HIGH-VOLTAGE p0-n0 HETEROJUNCTIONS BASED ON A LOW-DOPED GaAs LAYER - Sultanov A.M.; Abdukarimov A.A.; Bozorov X.N.; Boqiyev S.B.; Soatillayev A.U. (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation. Experiments have been carried out and the influence of Mn impurity on high-voltage p0-n0 heterojunctions based on a lightly doped gallium arsenide layer has been studied. The influence of Mn impurity on the position of the p0-n0 transition has been studied, the concentration and nature of the distribution of the main charge carriers have been determined, diffusion length of minority charge carriers, mobility of charge carriers, emergence of deep levels in a lightly doped gallium arsenide layer.